«Customed» justice: issues of condemning military people (XVI–XVII centuries) - O. V. Grigoriev (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of the problematic issues of the condemnation of military people in Russia in the XVI–XVII centuries. The activity of the administrative bodies is examined — orders that carried out diverse activities and, along with the functions of the central authority, administered justice to persons of the category under its jurisdiction. An attempt is made to consider some regulatory sources that formed the basis of the activities of military judicial authorities in Russia in the period under review, to analyze the procedure for the consideration of cases in a military court, to characterize the participants in the process. It is concluded that during the period under review, the judiciary was often in the hands of the military administration. The specific examples show the activities of military courts to maintain discipline and law and order in the army